2017
DOI: 10.1371/journal.pone.0175053
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus infection-induced inflammasome activation in human monocytes

Abstract: Inflammasomes are cytoplasmic sensors that regulate the activity of caspase-1 and the secretion of interleukin-1β (IL-1β) or interleukin-18 (IL-18) in response to foreign molecules, including viral pathogens. They are considered to be an important link between the innate and adaptive immune responses. However, the mechanism by which inflammasome activation occurs during primary Epstein-Barr virus (EBV) infection remains unknown. Human B lymphocytes and epithelial cells are major targets of EBV, although it can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 34 publications
1
38
0
1
Order By: Relevance
“…Viruses have been shown to evade AIM2 sensing possibly by inhibiting the ability of AIM2 to interact with released DNA. A recent study reported that Epstein–Barr virus (EBV) may activate AIM2 in THP1 cells . Two studies recently showed that influenza virus (IAV), a single stranded RNA virus, could trigger the release of endogenous DNA from damaged lung tissue possibly leading to AIM2 activation .…”
Section: Aim2 Detection Of Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses have been shown to evade AIM2 sensing possibly by inhibiting the ability of AIM2 to interact with released DNA. A recent study reported that Epstein–Barr virus (EBV) may activate AIM2 in THP1 cells . Two studies recently showed that influenza virus (IAV), a single stranded RNA virus, could trigger the release of endogenous DNA from damaged lung tissue possibly leading to AIM2 activation .…”
Section: Aim2 Detection Of Dnamentioning
confidence: 99%
“…A recent study reported that Epstein-Barr virus (EBV) may activate AIM2 in THP1 cells. 79 Two studies recently showed that influenza virus (IAV), a single stranded RNA virus, could trigger the release of endogenous DNA from damaged lung tissue possibly leading to AIM2 activation. 80,81 One study stated that AIM2 dampened detrimental inflammation in the lung microenvironment of mouse infected with IAV and that AIM2-deficient mice had exacerbated immune responses to IAV.…”
Section: Aim2 Detection Of Virusesmentioning
confidence: 99%
“…Under auxiliary adhesion molecules, the antigen polypeptide can be recognized and combined by T cell receptor on the surface of CTLS, which gradually induces the production of toxic protein that ultimately kills the target cells. EBV can induce the secretion of IL-1, IL-6, and TNF- α by monocytes; contribute to the production and maturation of dendritic cells; and promote the proliferation of virus-specific CTLs [26, 27]. EBNA-1 is the only nuclear protein that is expressed in all infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we observed a modest trend for a positive correlation between EBV shedding rate and levels of plasma sCD14. EBV infection has been shown to play a role in inflammasome activation in monocytes, [47] so it is possible that higher rates of EBV shedding can lead to more activated monocytes. Indeed, our results showed the HIV(+) group had higher levels of sCD14 as well as higher rates of EBV shedding.…”
Section: Discussionmentioning
confidence: 99%